2006
DOI: 10.1016/j.virol.2005.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide regulates SR protein phosphorylation during adenoviral infection

Abstract: In this study, we show that adenoviral infection induced accumulation of the sphingolipid ceramide in a dose- and time-dependent manner. This accumulation preceded cell lysis, occurred in the absence of biochemical evidence of apoptosis, and was derived from de novo synthesis of ceramide. An adenovirus mutant that lacks the adenovirus death protein (ADP) produced ceramide accumulation in the absence of cell lysis. This suggested that ceramide accumulation was either driven by adenovirus or was a cellular stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…The three RNA oligomers (r2, r3 and r6) derived from other regions in exon i9 did not or only minimally bind to SRSF3 protein (Supplementary Figure S3b). In agreement with the previous reports showing that the phosphorylation of SR splicing factors is required for their interaction with RNA, [63][64][65][66][67][68][69][70] dephosphorylation by treatment with calf intestine phosphatase abrogated the ability of SRSF3 to bind to RNA oligomers r1, r4 and r5 (data not shown). Introduction of mutations into the SRSF3 BS in RNA oligomers r1, r4 and r5 (r1*, r4* and r5*, Figure 4a) partially or fully abolished the binding of SRSF3 to these RNAs (Figure 4b).…”
Section: Srsf3 Regulatessupporting
confidence: 93%
“…The three RNA oligomers (r2, r3 and r6) derived from other regions in exon i9 did not or only minimally bind to SRSF3 protein (Supplementary Figure S3b). In agreement with the previous reports showing that the phosphorylation of SR splicing factors is required for their interaction with RNA, [63][64][65][66][67][68][69][70] dephosphorylation by treatment with calf intestine phosphatase abrogated the ability of SRSF3 to bind to RNA oligomers r1, r4 and r5 (data not shown). Introduction of mutations into the SRSF3 BS in RNA oligomers r1, r4 and r5 (r1*, r4* and r5*, Figure 4a) partially or fully abolished the binding of SRSF3 to these RNAs (Figure 4b).…”
Section: Srsf3 Regulatessupporting
confidence: 93%
“…As a possible mechanism, Kanj et al (25) reported recently that adenoviral infection causes an accumulation of ceramide, which results in the dephosphorylation of SR proteins. Because de novo ceramide synthesis by Fas activation or heat shock also causes dephosphorylation of SR proteins via the activation of PP1 (26), the viral infection may mimic the ceramide-medicated host pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Flp-In293 cells contained a single, stably integrated Flp recognition target site at a transcriptionally active locus. Briefly, mouse SRPK2 (mSRPK2) cDNA (25) or Venus was inserted into pcDNA5͞Flp recognition target͞V5-His-TOPO (Invitrogen) and transfected into Flp-In293 cells with pOG44 (Flp recombinase expression vector), resulting in the targeting integration of the expression vector. Then Flp-In293 cells stably expressing mock (Venus) or SRPK2 (SRPK2-2 or SRPK2-3) were selected and established as instructed.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that virus infection induces dephosphorylation and functional inactivation of SR proteins. As a possible mechanism, Kanj et al (13) have reported that adenoviral infection caused cellular accumulation of ceramide, which induces dephosphorylation of SR proteins by activation of the host pro- (32). Forty-eight hours after transfection, Western blotting was performed using anti-HA and anti-beta-actin antibodies.…”
Section: Vol 54 2010 Sr Protein Kinase Inhibitor Suppresses Hcv Repmentioning
confidence: 99%